Virus strain from a mild COVID-19 patient in Hangzhou represents a new trend in SARS-CoV-2 evolution potentially related to Furin cleavage site - Xi Jin; Kangli Xu; Penglei Jiang; Jiangshan Lian; Shaorui Hao; Hangping Yao; Hongyu Jia; Yimin Zhang; Lin Zheng; Nuoheng Zheng; Dong Chen; Jinmei Yao; et al. (Emerging Microbes and Infections, 2020)
ABSTRACTThe mutations in the SARS-CoV-2 virus genome during COVID-19 dissemination are unclear. In 788 COVID-19 patients from Zhejiang province, we observed decreased rate of severe/critical cases compared with patients in Wuhan. For mechanisms exploration, we isolated one strain of SARS-CoV-2 (ZJ01) from a mild COVID-19 patient. Thirty-five specific gene mutations were identified. Phylogenetic and relative synonymous codon usage analysis suggested that ZJ01 may be a potential evolutionary branch of SARS-CoV-2. We classified 54 global virus strains based on the base (C or T) at positions 8824 and 28247 while ZJ01 has T at both sites. The prediction of the Furin cleavage site (FCS) and sequence alignment indicated that the FCS may be an important site of coronavirus evolution. ZJ01 mutations identified near the FCS (F1-2) caused changes in the structure and electrostatic distribution of the S surface protein, further affecting the binding capacity of Furin. Single-cell sequencing and ACE2-Furin co-expression results confirmed that the Furin expression was especially higher in glands, liver, kidneys, and colon. The evolutionary pattern of SARS-CoV-2 towards FCS formation may result in its clinical symptom becoming closer to HKU-1 and OC43 caused mild flu-like symptoms, further showing its potential in differentiating into mild COVID-19 subtypes.